Evaluation Of Intervention on Voluntary Blood Donation Among 1st Prof Medical and Dental Students of Index Medical College, Indore (MP), India - Abhishek Bachhotiya; V K Arora; Piyusha Mahashabde (Medsci Publications, 2014)
Objective: Objectives of this study was to assess KAP regarding voluntary blood donation among 1stprof MBBS & BDS students of Index Medical College, Indore and also to evaluate the intervention in making the students aware about voluntary blood donation Methods: Among 209 students (125 MBBS, 84 BDS) a questionnaire was administered followed by participants' visit to the hospital blood donation centre where a short interactive awareness session was organized. The willingness to donate blood was noted at the end of the session. Results: All the participants had lack of knowledge regarding blood donation with no difference between male and female. The proportion of male blood donors was 36 (36.7%) while 9 (8.2%) female students had donated blood so far. At first, a total of 88 students were willing to donate blood, including those 45 who had earlier done it. Out of the 164 students who did not donate blood earlier, 24 (14.6%) had no support from family, 16 (9.75%) were afraid of needle prick, 34 (20.7%) had fear of becoming weak after blood donation and 8 (4.8%) were afraid of contracting any disease through needle prick. After the awareness session, a total of 196 students (93.77%) showed willingness to donate blood and the change was statistically significant. Conclusion: The knowledge and practice of voluntary blood donation among the study participants was found much better than the results of previous studies [7] and the awareness session-cum-visit to the blood donation centre fetched very high level of willingness. This implies the importance of regular intervention which can be most easily and successfully carried out by the teaching faculties in the medical college.